Effector CD4+ T cells recognize intravascular antigen presented by patrolling monocytes - Clare L. V. Westhorpe (Nature Portfolio, 2018)
Monocytes constitutively adhere and crawl along the glomerular endothelium and are thought to contribute to glomerulonephritis. Here the authors use multiphoton microscopy to show local antigen presentation by MHCII+ monocytes to T cells in glomerular capillaries of mice.